Efficient construction of a quinoline framework from alcohols, nitroarenes, and alkenes promoted by a trimetallic catalyst system - Rikiya Horikawa; Gen Onodera; Tsutomu Fukuda; Masanari Kimura (Tetrahedron Chem)
A Pd/Fe/In-trimetallic catalyst system promotes the three-component coupling reaction of primary alcohols, nitroarenes, and terminal alkenes to construct quinoline frameworks in a single operation. These consecutive coupling reactions proceed via an oxidative Povarov reaction of alkenes and aldimines derived from primary alcohols and nitroarenes by a redox hydrogen transfer system. This reaction may contribute to the efficient development of pharmaceuticals and medicinal products.